A PWM strategy for the modular structured multilevel inverter suitable for digital implementation - Aziz, J.A (2002)

(untitled)
A single carrier PWM strategy for a modular structured multilevel voltage source inverter is discussed in this paper. Using symmetric regular sampling technique, a multilevel modulation strategy is established to define the switching angles of the inverter switches. Mathematical equations for the PWM scheme suitable for digital implementation are derived. Finally simulation and hardware results are presented.